واقع التمكين الإداري وأثره في الأداء الوظيفي للعاملين بجامعة حفر الباطن في المملكة العربية السعودية: دراسة ميدانية - الشمري، عادل بن عايد (جامعة الكويت - مجلس النشر العلمي, 2021)
هدفت الدراسة الكشف عن مستوى التمكين الإداري والأداء الوظيفي للعاملين بجامعة حفر الباطن، وبيان أثر التمكين في هذا الأداء، وإن كانت هناك فروق ذات دلالة إحصائية في اتجاهات عينة الدراسة نحو التمكين الإداري والأداء الوظيفي تعزى لمتغير المسمى الوظيفي والمؤهل الدراسي وسنوات الخبرة والجنس. استخدم المنهج الوصفي التحليلي، واعتمدت الاستبانة أداة رئيسة لجمع بياناتها، ووزعت على عينة عشوائية بلغت 167 مفردة. وأظهرت الدراسة مجموعة من النتائج؛ أبرزها: وجود مستوى متوسط من التمكين الإداري، بينما جاء الأداء الوظيفي بمستوى عال. كما بينت النتائج وجود أثر إيجابي ذي دلالة إحصائية للتمكين الإداري في الأداء الوظيفي. وأوصت بمجموعة من التوصيات، أبرزها: التأكيد على أهمية تمكين الموظفين وتطوير مهاراتهم الإدارية، والاهتمام ببرامج التدريب المقدمة لهم، وبناء قاعدة بيانات تسهل عملية الاتصال والتواصل فيما بينهم.
The study aims to explore the level of administrative empowerment and job performance of the employees in Hafr Albatin University, and the impact of empowerment on this performance, and if there were significant differences in the orientations of the study sample towards administrative empowerment and job performance attributable to the variable of job title, qualification, years of experience and gender. The analytical descriptive approach was used, and the questionnaire was adopted as a main tool for collecting data. It was distributed to a random sample of 167 respondents. The study showed a number of results, the most prominent of which is: the existence of an average level of administrative empowerment, while the performance came at a high level. The results also showed a positive effect for administrative empowerment on performance. Recommendations are cited emphasizing the importance of empowering staff and developing their management skills, paying attention to training programs provided to them, as well as building a database to facilitate the process of communication and communication between them.
Keywords: الجامعات -- موظفي الجامعات -- الأداء الوظيفي -- التمكين الإداري -- الجامعات السعودية -- جامعة حفر الباطن